2016
DOI: 10.1186/s12889-016-3721-6
|View full text |Cite
|
Sign up to set email alerts
|

Defending behaviors, bullying roles, and their associations with mental health in junior high school students: a population-based study

Abstract: BackgroundStudents should be encouraged to help prevent or stop bullying. However, defending victims of bullying can impact on mental health. It is not only bystanders who may defend victims, but bullies, victims and bully-victims can also have defending behaviors. Nevertheless, most studies of defending behaviors have been limited to an examination of the reactions of bystanders or those not involved in bullying and have ignored the other players. The aim of this study is to investigate the associations betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 39 publications
(54 reference statements)
7
51
1
2
Order By: Relevance
“…This is in line with a study on the mental health implications of observing bullying, which found that witnessing victimisation has a significant negative impact on multiple indicators of mental health 18. There are several potential explanations for this finding.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This is in line with a study on the mental health implications of observing bullying, which found that witnessing victimisation has a significant negative impact on multiple indicators of mental health 18. There are several potential explanations for this finding.…”
Section: Discussionsupporting
confidence: 88%
“…It is possible that bystanders experience empathy towards the victim,14 which could in turn manifest as subjective health symptoms. When witnessing bullying, bystanders face peer pressure18 and risk a decrease in their social standing if they choose to intervene and help the victim. They also risk becoming a victim of bullying themselves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over time, bullying has become a serious public health problem affecting school-age children and adolescents 1,2 . It is characterized by intentional and repetitive aggressive behaviors in relationships where there is an imbalance of power 3 .…”
Section: Introductionmentioning
confidence: 99%